Saccharomyces cerevisiae in making halal products based on conventional biotechnology and genetic engineering - Tiara Khazalina (Journal of halal product and research (JPHR), 2020)
Indonesia is the nation with the world's largest Muslim population. Halal products is very important for the life of a Muslim. This includes the fulfillment of halal food, especially food-processed materials. Saccharomyces cerevisiae has contributed a lot in biotechnological processes in both conventional and modern biotechnology genetic engineering. Conventional biotechnology has been around since time immemorial by utilizing microbes for the manufacture of low-carbohydrate, long-lasting foods and drinks. The products produced also vary, some are halal or haram. Halal products such as bread, tape and bioethanol are used as fuel. Illegal products include intoxicating drinks such as sake. The development of modern biotechnology technologies that are currently developing such as genetic engineering in the manufacture of bioethanol which can be used as an alternative fuel that is environmentally friendly.